(untitled) (Eurasian Journal of Humanities and Social Sciences, 2024)
Central Asia, strategically located at the crossroads of Europe and Asia, plays a critical role in international cargo transportation. The region’s geopolitical importance, coupled with its vast energy resources and growing economies, underscores the need for efficient and wellmanaged cargo transport systems. This article examines the challenges and opportunities in organizing and managing international cargo transportation in Central Asia. It discusses the current state of infrastructure, policy frameworks, and logistical practices while highlighting the role of regional cooperation and technological innovation. Emphasis is placed on the integration of multimodal transport, digitalization, and sustainable practices to enhance efficiency and competitiveness in the global logistics market.